Pengaruh Non Performing Finance, Dana Pihak Ketiga dan Tingkat Bagi Hasil terhadap Pembiayaan Mudharabah Pada PT. Bank Syariah Mandiri, Tbk - Sugiharto Sugiharto (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
This research aims to determine the effect of NPFnet, DPK and TBH on Mudharabah Financing. The analytical approach uses quantitative methods with multiple regression analysis. Data collection techniques using secondary data sourced from PT. Bank Syariah Mandiri, Tbk. The results showed that the three factors such as NPF, DPK and TBH simultaneously had a positive effect on Mudharabah Financing at PT. Bank Syariah Mandiri during the period 2014 to 2018 for 20 quarters amounted to 70.60%, while the partial hypothesis test results prove that NPF and TPF have a significant effect on BSM mudharabah financing, while the profit sharing rate (TBH) has no significant effect.